2011
DOI: 10.1111/j.1600-0684.2010.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal synchronization of the menstrual cycles of pigtail macaques to facilitate biomedical research including modeling HIV susceptibility

Abstract: Progesterone and estradiol combination therapy can be used in pigtail macaques to induce synchronized cycling that persists in the absence of on-going hormone treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Menstrual cycling was monitored by visual observation and plasma progesterone 18 . Visual observations were recorded on every weekday throughout, and included menstrual blood and perineal tumescence (“sex skin swelling”, documented in 23 ). Plasma progesterone and MPA were measured at the Wisconsin National Primate Research Center, as previously described 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Menstrual cycling was monitored by visual observation and plasma progesterone 18 . Visual observations were recorded on every weekday throughout, and included menstrual blood and perineal tumescence (“sex skin swelling”, documented in 23 ). Plasma progesterone and MPA were measured at the Wisconsin National Primate Research Center, as previously described 18 .…”
Section: Methodsmentioning
confidence: 99%
“…We used a repeated-low-dose vaginal challenge macaque model. This model has several advantages, including the use of female pigtail macaques, which have a menstrual cycle and vaginal anatomy similar to those of women, an inoculum dose with viral RNA levels in the range similar to those detected in seminal fluid, twice-weekly challenges to mimic highrisk human exposure, and a SHIV-162p3 inoculum which constitutes an R5-tropic envelope similar to that of most transmitted HIV (14,22). We performed detailed PK analysis of intracellular TFV-DP drug levels in vaginal lymphocytes over time to better understand the relationship between tissue drug levels and protective efficacy.…”
mentioning
confidence: 99%
“…In PTM, we have shown that a desogestrel and ethinyl estradiol combined oral contraceptive (administered orally) suppress progesterone and estradiol. 40 MPA, given by injection, also suppresses progesterone and estradiol in PTM 47,48 (and E. Kersh, unpublished observations). Finding the human-equivalent dose of exogenous hormones requires extensive pharmacokinetic and pharmacodynamic studies over several months, using a combination of measures including levels of proges- terone and estradiol and vaginal thinning.…”
Section: Types Of Non-human Primate Models For Studying How Hormonal mentioning
confidence: 81%
“…Table I indicates other features of RM and PTM macaque models that may be relevant in studies of HC and HIV susceptibility. Menstrual cycle synchronization of a group of macaques, often used to facilitate breeding in agricultural animals, can be induced using shortterm hormonal contraception, as we have shown in PTM 40 and can be carried out in RM (M. Lewis, personal communication). Animals then continue on synchronized cycles for months in the absence of any exogenous reproductive hormone.…”
Section: Types Of Non-human Primate Models For Studying How Hormonal mentioning
confidence: 99%